Different FDG-PET metabolic patterns at single-subject level in the behavioral variant of fronto-temporal dementia. (October 2016) - Cerami, Chiara; Dodich, Alessandra; Lettieri, Giada; Iannaccone, Sandro; Magnani, Giuseppe; Marcone, Alessandra; Gianolli, Luigi; Cappa, Stefano F.; Perani, Daniela
Abstract: Background: The diagnosis of probable behavioral variant of fronto-temporal dementia (bvFTD) according to current criteria requires the imaging evidence of frontal and/or anterior temporal atrophy or hypoperfusion/hypometabolism. Different variants of this pattern of brain involvement may, however, be found in individual cases, supporting the presence of heterogeneous phenotypes. Objective: We examined in a case-by-case approach the FDG-PET metabolic patterns of patients fulfilling clinical criteria for probable bvFTD, assessing the presence and frequency of specific FDG-PET features. Materials and methods: Fifty two FDG-PET scans of probable bvFTD patients were retrospectively analyzed together with clinical and neuropsychological data. Neuroimaging experts rated the FDG-PET hypometabolism maps obtained at the single-subject level with optimized voxel-based Statistical Parametric Mapping (SPM). The functional metabolic heterogeneity was further tested by hierarchical cluster analysis and principal component analysis (PCA). Results: Both the SPM maps and cluster analysis identified two major variants of cerebral hypometabolism, namely the "frontal" and the "temporo-limbic", which were correlated with different cognitive profiles. Executive and language deficits were the cognitive hallmark in the "frontal" subgroup, while poor encoding and recall on long-term memory tasks was typical of the "temporo-limbic" subgroup. Discussion: SPM single-subject analysis indicates distinct patterns of brain dysfunction in bvFTD, coupled with specific clinical features, suggesting different profiles of neurodegenerative vulnerability. These findings have important implications for the early diagnosis of bvFTD and for the application of the recent international consensus criteria.